SO Challenges facing local authorities in light of the Corona pandemic and its relationship with the central government in Palestine: local authorities - Obaid, Shaher (Archives of Business Research, 2020)
The research seeks to give a detailed description of the current state of affairs within the local authorities in Palestine. Notably, the issues that are explicitly addressed are how the pandemic has affected the local authorities; capacity to offer essential services to the citizens. A cross-sectional study involving senior employees at Al-Bireh Municipality, the citizens from Al-Bireh Municipality and head of the Emergency Committee in Palestinian Cities and villages was applied to help gain a proper understanding of the extent to which the pandemic has negatively impacted the local authorities’ abilities to offer services to the citizens. The results have shown that the pandemic has limited delivery of crucial roles such as environmental services, water services, and solid waste elimination, among others. Additionally, the challenges facing the local authorities in the face of this pandemic have been highlighted as shorted finance, human resources and necessary equipment. Finally, a recommendation section is included to address some of the measures that the local authorities can implement to prevent the effects associated with the occurrence of the pandemic.